2015
DOI: 10.1111/geb.12296
|View full text |Cite
|
Sign up to set email alerts
|

Global effects of soil and climate on leaf photosynthetic traits and rates

Abstract: AimThe influence of soil properties on photosynthetic traits in higher plants is poorly quantified in comparison with that of climate. We address this situation by quantifying the unique and joint contributions to global leaf-trait variation from soils and climate.Location Terrestrial ecosystems world-wide.Methods Using a trait dataset comprising 1509 species from 288 sites, with climate and soil data derived from global datasets, we quantified the effects of 20 soil and 26 climate variables on light-saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
322
6
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 299 publications
(396 citation statements)
references
References 47 publications
(74 reference statements)
38
322
6
6
Order By: Relevance
“…4), despite the fact that phenological variation has been reported for some foliar traits ; but see Fajardo and Siefert, 2016). Lithology did not appreciably improve MICE imputations, in contrast to the reported influence of soil pH on some foliar traits (Maire et al, 2015;Simpson et al, 2016).…”
Section: Mice Imputations Using Different Levels Of Environmental Infmentioning
confidence: 85%
“…4), despite the fact that phenological variation has been reported for some foliar traits ; but see Fajardo and Siefert, 2016). Lithology did not appreciably improve MICE imputations, in contrast to the reported influence of soil pH on some foliar traits (Maire et al, 2015;Simpson et al, 2016).…”
Section: Mice Imputations Using Different Levels Of Environmental Infmentioning
confidence: 85%
“…2) and photosynthetic capacity can depend on the time of year. Recent work relating photosynthetic capacity to climate variables, environmental factors, and soil conditions shows promise for better capturing the dynamic nature of this parameter (e.g., Verheijen et al, 2013;Ali et al, 2015;Maire et al, 2015).…”
Section: Future Development Prioritiesmentioning
confidence: 99%
“…At the global scale, it has been recently shown that strategies of nitrogen and water acquisition are independent. They co-vary with independent soil dimensions (soil pH and soil available phosphorus) and they both lead to increased leaf photosynthetic rate (Maire et al 2015, but see Reich 2014 defining water-nitrogen strategies at a local scale). How each resource is linked with a specific strategy of resource capture is a further step to investigate in order to better predict the interactive effects of multiple resource gradients.…”
Section: Grass Strategies Along Nutrient Gradientsmentioning
confidence: 99%
“…Considering the independent dimensions of environment will also help to better understand the different selection forces for plant functional traits. For instance, leaf nitrogen content increases both with soil fertility and climatic aridity (Maire et al 2015). In grasslands, the herbivory pressure and the management can be considered as additional dimensions of the environment to which species will respond.…”
Section: Which Assembly Process For Which Conditions?mentioning
confidence: 99%